With a little help from my old T cell: Memory follicular T helper cells driving autoimmunity? - Winkler, Thomas; Waisman, Ari (European journal of immunology, 2014)
It has long been known that the B cell repertoire includes cells that are capable of producing autoantibodies and that these cells can be found in humans and also in wild type strains of laboratory mice; however, normally, these B cells do not give rise to plasma cells, and thus do not fulfil their autoimmune potential. In this issue of the European Journal of Immunology, Nusser et al. [Eur. J. Immunol. 2014. 44: 2893-2902] dissect the mechanism by which these B cells are activated and autoantibodies are produced. The authors demonstrate that T cells, most likely antigen-specific, which accumulate with age or as a result of homeostatic proliferation, provide essential help to these autoreactive B cells. Hence, this study reveals a previously under appreciated mechanism, by which T cells, possibly generated with age after exposure to a variety of antigens, break immunological tolerance and lead to the generation of autoantibodies that could contribute to the development of autoimmune diseases.
Keywords: Antibodies; Autoimmunity; CD4+ T cells; Tolerance